Gold nanoparticle array formation on dimpled Ta templates using pulsed laser-induced thin film dewetting. Issue 16 (28th April 2015) - El-Sayed, Hany A.; Horwood, Corie A.; Owusu-Ansah, Ebenezer; Shi, Yujun J.; Birss, Viola I.
<x xml:space="preserve">Abstract</x> Au nanoparticle array formed on a dimpled Ta template using laser-induced thin film dewetting.